Agreement between the nutritional status of schoolchildren and the perception of their guardians - Coccaro PIVATTO, Bianca; Azeredo de LIMA, Lena (Revista de Nutrição, 2023)
Objective Assess the correlation between classification of nutritional status of schoolchildren and the perception of their guardians. Methods A cross-sectional study with children aged 6-10 years from a public school in the South of Brazil. Weight and height of the schoolchildren were collected, and the guardians answered a questionnaire containing the range of silhouettes of Brazilian children. The perception through the scale of silhouettes was compared with the actual nutritional status. Kappa coefficient was used to check the consistency of actual and perceived perception. The prevalence ratio was calculated between perceived overweight and well-nourished children. Results A total of 236 guardians of schoolchildren were interviewed. The level of agreement between the nutritional status assessment of actual and perceived perception was weak (Kappa=0.32, p<0.001). As for the perception of nutritional status, 50.8% of the guardians scored the nutritional rating their children correctly, of which 42.0% of these children were overweight and 60.2% were well-nourished, p<0.05. The prevalence of guardians who underestimated the classification of the nutritional status was 21.6%, and underestimation of overweightchildren was 1.8 times greater than of well-nourished children. The overestimation of the nutritional status was 27.5%. The most prevalent nutritional status was well-nourished, followed by overweight. Conclusion The study showed that guardians do not have the correct perception of the nutritional status of the schoolchildren. Public interventions for health education must be conducted to reduce erroneous perceptions.